Cardiorenal Protection With the Newer Antidiabetic Agents in Patients With Diabetes and Chronic Kidney Disease: A Scientific Statement From the American Heart Association. Issue 17 (27th October 2020) - Rangaswami, Janani; Bhalla, Vivek; de Boer, Ian H.; Staruschenko, Alexander; Sharp, Johanna A.; Singh, Radhika Rajgopal; Lo, Kevin Bryan; Tuttle, Katherine; Vaduganathan, Muthiah; Ventura, Hector; McCullough, Peter A.
Abstract : Chronic kidney disease (CKD) with type 2 diabetes (T2D) is a major public health problem, resulting in significant cardiovascular and kidney adverse outcomes worldwide. Despite the widespread use of standard-of-care therapies for CKD with T2D over the past few decades, rates of progression to end-stage kidney disease remain high with no beneficial impact on its accompanying burden of cardiovascular disease. The advent of the newer classes of antihyperglycemic agents, including SGLT2 (sodium glucose cotransporter 2) inhibitors and GLP-1 (glucagon-like peptide-1) receptor agonists, has changed the landscape of therapeutic options for patients with CKD with T2D, with demonstration of significant reductions in cardiovascular adverse events and progression to end-stage kidney disease. Several potential mechanisms exist through which these beneficial effects are achieved in both drug classes, which may be independent of their antihyperglycemic effects. This scientific statement summarizes the current literature on the cardiorenal protective effects with SGLT2 inhibitors and GLP-1 receptor agonists in patients with CKD and T2D. It reviews potential mechanistic pathways that may drive these benefits and summarizes the literature on adverse effects in patients with CKD and T2D at risk for or with established cardiovascular disease. Last, it provides practical guidance on a proposed collaborative care model bridging cardiologists, nephrologists, endocrinologists, and primary care physicians to facilitate the prompt and appropriate integration of these therapeutic classes in the management of patients with T2D and CKD. Abstract : Supplemental Digital Content is available in the text.